PENGARUH INTELLECTUAL CAPITAL DAN CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Anisa Hediyanti Muasiri; Erna Sulistyowati (Politeknik Bisnis Indonesia, 2021)
This study aims to test the influence of intellectual capital and corporate governance on firm value with profitability as a moderating variable. The population of this study is banking companies listed on IDX during 2015 – 2019 amounted to 45 companies. Sampling techniques using purposive sampling so that research samples obtained as many as 15 companies. The research data used is secondary data obtained from the annual report and GCG report of banking companies listed on IDX during 2015 – 2019. This study uses structural equation modeling data analysis technique – partial least square (SEM-PLS) with WarpPLS 7.0 software. The result of this study shows that: (1) Intellectual capital positively and significantly affects the firm value, (2) Corporate governance has no effect on the firm value, (3) Profitability can moderate the influence of intellectual capital on the firm value, (4) Profitability can’t moderate the influence of corporate governance on the firm value.